Efeitos da época de dobramento da planta e da época de colheita sobre o rendimento de grãos do milho - SILVA, PAULO SERGIO LIMA E; OLIVEIRA, FABIO HENRIQUE TAVARES DE; ABREU, JOSÉ UILSON ALBUQUERQUE; SILVA, KATHIA AMRIA BARBOSA E (Revista Ceres, 2015)
.